The Study of Kinetics of Diffusion and Phase Formation in the Layered Iron-Beryllium System - Kuterbekov, K. A.; Nurkenov, S. A.; Kislitsin, S. B.; Kuketayev, T. A.; Nurakhmetov, T. N. (Springer US, 2017)
The methods of Mössbauer spectroscopy with X-ray phase analysis and Rutherford backscattering of protons were used to study the kinetics of diffusion and phase transformations in the layered iron-beryllium system. For the first time, the authors suggested and implemented a method for retardation of diffusion and phase formation processes in the layered iron-beryllium system using the barrier layer. It was established that the barrier layer limits the zone of beryllium dissolution in the area of implanted layer. The impact of the barrier layer on kinetics of thermally induced processes of diffusion and phase transformations in the layered Fe–Be system was determined using the example of Fe (10 μm): O+ – Be (0.7 μm) – 57Fe (0.1 μm). The authors suggested and implemented a method for recovery of the distribution function of the admixture atom concentration in the solid matrix–admixture solution on the basis of the X-ray diffraction data. The kinetics of mutual diffusion was determined for Fe and Be atoms in the α-Fe(Be) solution for both sides of the layered systems with a barrier layer and without it using the suggested method for recovery of the distribution function of the Be atom concentration. It was established that for the system without a barrier layer, the share of iron atoms ends at tann ~ 5 h on the coating side and at tann ~ 7.5 h on the iron side, while for the barrier layer case – at tann ~ 20 h on the coating side and at tann ~ 40 h on the iron side.
Keywords: barrier layer; diffusion process kinetics; phase formation; thermal annealing; phase transformations; intermetallic compounds